Pallidal 1/f asymmetry in patients with cervical dystonia. (2nd May 2020) - Semenova, Ulia; Popov, Valentin; Tomskiy, Alexey; Shaikh, Aasef G.; Sedov, Alexey
Abstract: Lateralized differences in pallidal outflow are putatively linked to asymmetric tonic contractions of the neck muscles in cervical dystonia (CD). At the population level, the interhemispheric asymmetry has been traditionally studied for the estimation of the spectral power in specified frequency bands. Broadband spectral features, however, were not taken into consideration. The contemporary analysis revealed that the aperiodic (1/f) broadband activity could be a neurophysiological marker of the excitation/inhibition ratio. During deep brain stimulation (DBS) surgery, we measured bilateral pallidal local field potentials (LFP) in nine CD patients, examining the effects of lateralized asymmetry on 1/f broadband activity. All patients showed a trend towards an asymmetric difference in the 1/f broadband activity. The ipsilateral 1/f slope was significantly higher in internal (GPi) segment of the globus pallidus that is on the contralateral side of the direction of the dystonia. We also found lateralized differences in the beta oscillations for GPi and in the alpha oscillations for GPe. Our findings emphasize the importance of mainstreaming broadband activity in the estimation of LFP spectral features together with periodic features and provide further evidence for the pallidal asymmetry in CD patients. Abstract : Lateralised differences in pallidal outflow are assumed to be linked to asymmetric pathological tension of the neck muscles in cervical dystonia (CD). The contemporary analyses show that the aperiodic (1/f) broadband activity could be a neurophysiological marker of the excitation/inhibition ratio. We found asymmetry of 1/f slope in the globus pallidus internal (GPi), which may reflect the feedback imbalance to head neuronal integrator and subsequent dysfunction.